问题
解答题
计算: (1)-3-6+9-11+2 (2)(
(3)(-10)-(-10)×
(4)(-1)3-(1-0.5)×
(5)(-12)÷(-
(6)8+(4-5)÷0.1 (7)-14-(1-0.5)×[2-(-3)2] (8)36×(
(9)3.14×(-5)+3.14×(-12)+3.14×8 |
答案
(1)原式=(-3-6-11)+(2+9)
=-20+11
=-9;
(2)原式=
×(-24)-1 6
×(-24)+3 4
×(-24)1 12
=-4+18-2
=14-2
=12;
(3)原式=-10-(-5)×
×(-20)1 2
=-10-50
=-60;
(4)原式=-1-
×1 2
×(2-9)1 3
=-1+7 6
=
;1 6
(5)原式=(-12)×(-12)×(-
)1 100
=144×(-
)1 100
=-1.44;
(6)原式=8+(-1)×10
=8-10
=-2;
(7)原式=-1-
×(2-9)1 2
=-1+7 2
=
;5 2
(8)原式=36×(
)21 6
=36×1 36
=1;
(9)原式=3.14×(-5-12+8)
=3.14×(-9)
=-28.26.